Elaboración del Mapa de Análisis de la Distribución de Especies Vegetales del Bosque Húmedo Pie Montano de la Zona Noroccidental de la Provincia de Cotopaxi - Vallejo Ronquillo, Jorge Wladimir (2018)
In the ever humid piedmont forest of the northwestern Cotopaxi mountain range in the plots established inside 3 different altitudinal floors that are a part of the project area of the germoplasm bank of the Environmental Engineering career in Cotopaxi Technical University, the research work was carried out regarding four tree species: Myrcia sp (White Arrayan), Persea Caerulea (Aguacatillo), Benthamiana Sp. (Canelo) and Alchornea Glandulosa (Manzano), and subsequently the analysis map that represents the distribution of these species within the plots, for this reason spatial positioning techniques, computerized programs were applied and finally the interpretation of the map was made. As a result of the investigation and after obtaining the percentage of relative abundance, it was deduced that there are distribution patterns, which refer to the dispersion of individuals from a population in space at a given time, the individual organisms that make up a population they can be distributed in some ways: more or less uniform, scattered randomly or forming groups. In this case the species were analyzed according to the distribution patterns such as: Myrcia sp (White Arrayan), Persea Caerulea (Aguacatillo), Benthamiana Sp. (Canelo), are randomly distributed and Alchornea Glandulosa (Apple tree) ), is distributed in a grouped way, which is a significant fact taking into account that this distribution is repeated in three plots at different heights, something that may give rise to a new investigation that focuses on studying the reason of the grouped form that the Manzano was found